PWE-074 Tissue Inhibitor Of Metalloproteinase (timp)-3 Reduces Pro-inflammatory Cytokine Production By Ulcerative Colitis Mucosa Cultured Ex Vivo. (9th June 2014) - Bell, IM; Ammoscato, F; Biancheri, P; Curciarello, R; Macdonald, T
Abstract : Introduction: Interleukin (IL)-1b, IL-6, IL-8 and tumour necrosis factor (TNF)-a, are elevated in the inflamed mucosa of patients with ulcerative colitis and play a central role in driving the pro-inflammatory immune response in this condition. TNF-a is cleaved from the cell surface by TNF-a converting enzyme (TACE), which is inhibited by tissue inhibitor of Metalloproteinase (TIMP)-3. We studied whether the addition of TIMP-3 to inflamed colonic biopsies from ulcerative colitis patients reduced the release of the pro-inflammatory cytokines TNF-a, IL-1b, IL-6 and IL-8. Methods: Colonic biopsies were obtained from macroscopically inflamed areas of 4 patients with ulcerative colitis undergoing colonoscopy for a disease flare. Biopsies were then cultured ex vivo for 24 h in 300 ul of serum free HL-1 medium in the absence or presence of recombinant human TIMP-3 (100 ng/ml). The concentration of TNF-a, IL-1β, IL-6 and IL-8 were measured in culture supernatants by ELISA. Results: Culture with TIMP-3 significantly reduced TNF-a production by inflamed ulcerative colitis biopsies cultured ex vivo (from 1365 ug/ml in the absence of TIMP-3 to 45 ug/ml after TIMP-3 addition). Furthermore, the addition of TIMP-3 significantly reduced IL-1b production by inflamed ulcerative colitis biopsies (from 776 to 261 ug/ml). There was a trend in the reduction of IL-6 (from 3018 to 2702 ug/ml), which did not reach statistic significance, and no significant change in IL-8 production (from 30812 to 29114.5 ug/ml). Conclusion: TIMP-3 administration not only causes a reduction in TNF-a via TACE inhibition but also IL-1β. This raises the possibility of its use therapeutically in the treatment of ulcerative colitis. Disclosure of Interest: None Declared.